Integrating Legal Protection Strategies for Wife and Children Due to Rejection of Marriage Isbat Application - Jalil, Abdul; Abdul Haq Syawqi; M. Haris Hidayatulloh; Supraptiningsih, Umi; Cut Linda Marheni (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study explores integrative legal protection strategies for wives and children, bridging normative and sociological perspectives, in the face of Isbat Nikah application rejections. This strategy is essential because it is motivated by the facts in the field, namely that many Isbat Nikah are not registered and have legal consequences. This study uses a qualitative approach; this empirical study is drawn from observation data and interviews with judges and clerks in three religious courts (PA) in East Java, namely in Pamekasan, Probolinggo, and Pasuruan Districts. The data was further enriched by comparing it with document and literature studies, then analyzed using descriptive techniques. This article finds that the legal protection of wives and children due to the rejection of Isbat Nikah applications is to apply an integrative normative-sociological strategy. Normatively, the way that can be taken is by integrating several aspects such as aspects of the law, law enforcement, and facilities or facilities that can support the application of law, such as human resources and sophisticated tools such as tools to find out a person's DNA. Meanwhile, sociologically, two aspects of social problems are crucial to carrying out an integrated improvement strategy, namely aspects such as aspects of a religious-type society and a negative patriarchal culture. Religious communities often exhibit a strong susceptibility to dependence on religious guidance.